2a) Vn+1=(Un+1-3)/(Un+1-1)
Un+1-3=(5Un-3)/(Un+1)-3=(5Un-3-3Un-3)/(Un+1)=(2Un-6)/(Un+1)=2(Un-3)/(Un+1)
Un+1-1=(5Un-3)/(Un+1)-1=(5Un-3-Un-1)/(Un+1)=(4Un-4)/(Un+1)=4(Un-1)/(Un+1)
Donc Vn+1=2(Un-3)/(Un+1)*(Un+1)/4(Un-1)=1/2*(Un-3)/(Un-1)
Vn+1/Vn=1/2*(Un-3)/(Un-1)*Un-1)/(Un-3)=1/2
Donc Vn est géométrique de raison 1/2
2b) Vo=(Uo-3)/(Uo-1)=3
Donc Vn=3*(1/2)^n=3*0,5^n
3) Vn=(Un-3)/(Un-1)=(Un-1-2)/(Un-1)=1-2/(Un-1)
On a donc 3*0,5^n=1-2/(Un-1)
Donc 2/(Un-1)=1-3*0,5^n
Un-1=2/(1-3*0,5^n)
Un=1+2/(1-3*0,5^n)